Electoral campaign of mayor candidates of Tigbauan, Iloilo in the 1992 election. - Minerva, Marie Iris Magdalene T
This is a descriptive study of the electoral campaign of the six mayoral candidates of Tigbauan in the 1992 election. The study focuses on the important features of an electoral campaign, such as campaign resources, campaign organization and campaign strategies. In undertaking the study, the researcher interviewed the mayoral candidates, their family members, their campaign staff and/or their representatives. A questionnaire was administered to a sample of voters. The important findings of the study are: "mayorables" came from prominent families, with almost all of them having finished their college education; these "mayorables" have had their experience with politics before they ran as mayor; a mayoral candidate's campaign resources, more particularly is material resources, are said to be the ultimate factor in the success of his electoral campaign primarily because election campaigns have become expensive since vote-buying has become ever more common; The organization of an electoral campaign at the municipal level is not formally structured; contrary to the general view that local elections are highly personal, the 1992 Tigbauan mayoral election did not focus on personal issues or controversies and in fact, mud-slinging and character assassination were practically absent; although mayoral candidates have acknowledged the fact that there was vote-buying, yet they considered the 1992 election peaceful.